Doping efficiency and limits in (Mg, Zn)O:Al, Ga thin films with two‐dimensional lateral composition spread. Issue 12 (28th August 2015) - Mavlonov, Abdurashid; Richter, Steffen; von Wenckstern, Holger; Schmidt‐Grund, Rüdiger; Lenzner, Jörg; Lorenz, Michael; Grundmann, Marius
Abstract: We have investigated structural, optical, and electrical properties of Mg x Zn 1 − x O:(Al/Ga) thin films in dependence on Mg and Al/Ga concentrations. For this purpose, thin films with two perpendicular, lateral composition gradients, i.e., the Mg composition is varied in one direction whereas the Al/Ga concentration is varied in a perpendicular direction were grown at 600 ∘ C by pulsed‐laser deposition (PLD) using a threefold segmented PLD target and 2‐inch in diameter c ‐plane sapphire substrates. It has been found that compensation by intrinsic acceptors limits efficient doping to dopant concentrations of about 2 × 10 21 cm − 3 . Further, the electrical data suggests, that the compensating defect is doubly chargeable hinting to the zinc vacancy as microscopic origin. Increasing the dopant concentration above 2 × 10 21 cm − 3 leads to a degradation of electrical and structural properties.